Peer Victimization and Aggressive Behavior Among Chinese Adolescents: Delinquent Peer Affiliation as a Mediator and Parental Knowledge as a Moderator - Lin, Shuang; Yu, Chengfu; Chen, Weiqi; Tian, Yunlong; Zhang, Wei (Frontiers in Psychology, 2018)
Grounded in social network theory and a risk-buffering model, this study examined whether delinquent peer affiliation mediated the association between peer victimization and adolescent aggressive behavior and whether this mediating process was moderated by parental knowledge. A total of 4,209 Chinese adolescents (48.47% male, Mage = 13.68) completed questionnaires on peer victimization, parental knowledge, delinquent peer affiliation, and adolescent aggressive behavior. Path analyses showed that delinquent peer affiliation partially mediated the relationship between peer victimization and aggressive behavior. Moreover, parental knowledge had a protective effect of buffering the adverse influence of peer victimization on aggressive behavior. This indirect link was stronger for adolescents with low parental knowledge than for those with high parental knowledge. This finding highlights delinquent peer affiliation as a potential link between peer victimization and aggressive behavior and provides an effective intervention for addressing the adverse effects of peer victimization.